Naked guide to bonds : - Brandes, Michael V. (Wiley, 2003)
Fixed income can be an enormously complex and confusing asset class–even for seasoned investment professionals–with a dizzying array of instruments and strategies. Fortunately, Brandes has done a marvelous job of pulling back the proverbial curtain, to unveil and demystify the bond market by breaking a complicated topic down into simple, manageable, and understandable building blocks.